Determination of Mercury, Cadmium, Tin and Nickel in Three Canned Tuna in Iran - Motaghifar, Afshin; Hosseinzadeh, Khorshid; Shafipour, Hooman; Shohre, Polin; Nasiri, Davoud; Tavakoli Vaskas, Abbas (Asian Journal of Chemistry, 2013)
Considering the importance of fish and its related products to meet the needs of the people to protein and other minerals as well as the impact of infected aquatic ecosystems on the fish infestation are the subject of interest. The presence of heavy metals as the result of industrial pumping and environmental contamination in sea food products such as tuna, measuring the existing heavy metals levels in the aquatic environment can serve as a suitable indicator of water pollution and the quality of these food and the risks of their being poisoned with heavy metals can be considered accordingly. This research was conducted on 21 samples of canned tuna selected randomly from the three factories producing canned tuna namely Shilton, Teihou and Telaji in 2011. After transferring the samples to the laboratory and digesting them, they were analyzed for heavy metals including mercury, tin, cadmium and nickel through atomic absorption technique. The highest and lowest amount of mercury and nickel were observed in the manufacturing factories of Telaji and Shilton, respectively and the highest and lowest amounts of cadmium and tin were related to the manufacturing factories of Teihou and Shilton, respectively. The results showed that the amount of the given heavy metals in the products of these factories were lower than the standards set by FDA, EPA, FAO/WHO and are not detrimental to human's health.